SUMBER DAYA MANUSIA DALAM IMPLEMENTASI KAPITASI BERBASIS PEMENUHAN KOMITMEN PELAYANAN PUSKESMAS - Surya Fahmil; Iting Iting (HSG (Health Science Growth) Journal, 2021)
One of the efforts to improve the quality health service of community health centers in the implementation of the national health insurance program is to implement a commitment-based capitation payment, but in its implementation there are many community health center that cannot achieve the capitation payment target that must be received by the community health center as the first health facility. KBPK implementer A qualitative descriptive research has been carried out with a case study approach at the community health centers in Langkat Regency, with the aim of providing the availability of human resources at the community health centers in the context of implementing the KBPKP by utilizing information, including: Head of community health centesr, P-Care Officer, and Person in Charge at the Office Health and BPJS Health Langkat Regency. The results of the study indicate that human resources are sufficient in terms of numbers, but inadequate in terms of expertise and time. It is recommended to conduct an assessment of the performance of community health centers officers related to the implementation of KBPKP in community health centers and other variables that need to be investigated. Keywords : power, human capitation, resources